2022
DOI: 10.1039/d2cy00984f
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric induced reverse photocatalytic performances of carbon nitride with different structures

Abstract: Piezoelectric assisted photocatalysis has emerged as an effective way to achieve higher utilization of charge carriers through the introduction of internal electric field. Even though in its infancy, the piezoelectric...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The reason for the increase in catalyst activity was further investigated by the following characterization methods 49–51 . The arc radius corresponding to 1% ZSO/BWO is smaller than that of pure BWO (Figure 9a) because its internal charge transfer speed is fast 52–54 .…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for the increase in catalyst activity was further investigated by the following characterization methods 49–51 . The arc radius corresponding to 1% ZSO/BWO is smaller than that of pure BWO (Figure 9a) because its internal charge transfer speed is fast 52–54 .…”
Section: Results and Analysismentioning
confidence: 99%
“…The reason for the increase in catalyst activity was further investigated by the following characterization methods. [49][50][51] The arc radius corresponding to 1% ZSO/BWO is smaller than that of pure BWO (Figure 9a) because its internal charge transfer speed is fast. [52][53][54] Subsequently, the fast photo-generated charges transmission for the 1% ZSO/BWO composite is attributed to a lower overpotential over the whole voltage range, 55 and the photocurrent of 1% ZSO/BWO is stronger than that of pure BWO, which indicates that the piezoelectric field can effectively accelerate the carrier separation of 1% ZSO/BWO (Figure 9b).…”
Section: Piezo-photocatalysis Mechanismmentioning
confidence: 99%
“…To investigate the impact of different structures on the performance of g-C 3 N 4 piezoelectric catalytic materials, Zhang et al conducted detailed studies on the piezoelectric properties and piezoelectric-assisted photocatalytic performance of three different structural GCNs: melon-like, polyheptazine imide (PHI), and polytriazine imide (PTI). 155 The results showed that under ultrasonic action, polytriazine imide (PTI) demonstrated the best piezocatalytic performance in typical potassium permanganate reduction and hydrogen peroxide generation reactions. Furthermore, the morphology significantly impacts the piezoelectric performance of PTI.…”
Section: Carbon Nitridementioning
confidence: 99%
“…Recent interest has led to the examination of the potential of graphitic carbon nitride to produce hydrogen peroxide and degrade water pollutants when used as either a piezocatalyst [4,[18][19][20] or a piezophotocatalyst. [21][22][23] However, studies to date have primarily used a high catalyst dosage, varying from 0.5 [4] to 1 g L À1 ; [18,19] such a high catalyst dosage level results in the need for additional stirring to prevent the catalyst from depositing at the base of the reactor. It has been reported that the use of an agitator can lead to fluctuations in the propagation of ultrasonic waves.…”
Section: Introductionmentioning
confidence: 99%